Dokumenty kartograficzne z początków Aleksandrowa Łódzkiego - Kowalski, Grzegorz; Kowalski, Rafał (Wydawnictwo Politechniki Łódzkiej, 2010)
W opracowaniu scharakteryzowano zasób informacji zawarty w dwóch dokumentach kartograficznych z początków XIX wieku a dotyczących założenia miasta Aleksandrowa Łódzkiego.

The study characterized the recource of information contained in two mapping documents drawn in the early of nineteen century. The documents concern the founding of the city Aleksandrów Łódzki.
Cartographic documents of the early city Aleksandrów Łódzki